Influence of pH, Shaked Medium, and Addition of Sawdust on the Growth of Xylaria sp. - Achmad .; Elis Nina Herliyana; Eti Artiningsih Octaviani (Jurnal Silvikultur Tropika, 2013)
Fungi is natural resources that has many potencies to be developed to fill the human’s need. One of useful fungal species is Xylaria sp. as a decomposer which play an important role in the process of returning nutrients in to the soil. This reasearch aims to examine the effect of medium pH, medium movement, and sawdust of Sengon (Falcataria molucana) & Afrika wood (Maesopsis eminii) addition in medium on the growth of Xylaria sp. Each experiment used Completely Randomized Design with 3 replications. The result showed that best Xylaria sp. colony on PDA attained at pH 8; at pH 2 the fungi did not grow. Highest mycelial dry weight of Xylaria sp. in PDB medium with pH treatment was achieved at pH 6. Highest mycelial dry weight of Xylaria sp. in PDB with shaking was achieved at a speed of 100 rpm. The addition of sawdust in MEA medium did not significantly affect the growth of mycelial diameter of Xylaria sp.Key words: africa wood, medium movement, pH, sengon, Xylaria sp